ICE BREAKING TO IMPROVE ENGLISH SPEAKING SKILLS IN PRATHOM STUDENTS AT MAITREECHIT WITTAYATHAN SCHOOL BANGKOK THAILAND - Santoso, Yolanda Marsha; Mega Febriani Sya; Abdul Kholik (Fakultas Agama Islam dan Pendidikan Guru, 2024)
The importance of improving English speaking skills in early childhood as a foundation for forming their identity. The aim of this research is to find out howice breaking in improving the English speaking skills of Prathom students at Maitreechit Wittayathan School Bangkok Thailand. This research uses a qualitative approach. With a qualitative descriptive method. Data sources were taken from documentation, interview results, and participant observation results. The validation technique in this research uses triangulation techniques. The research results show that the use of icebreaking improves English speaking skills based on the results of interviews with teachers, students, and participant observations. It can be concluded that ice-breaking tailored to achieving goals can effectively stimulate the development of English-speaking skills.